Inserción laboral de los graduados de la carrera de Nutrición y Salud Comunitaria de la Universidad Técnica Del Norte, periodo 2014 - 2018: Labor insertion of the graduates of the Carrera de Nutrición y Salud Comunitaria of the Universidad Técnica del Norte, periodo 2014 - 2018a, 2016 (La U Investiga, 2019)
This study responds to the requirements established by the Ley Orgánica de Educación Superior (LOES), the objective was to follow up on the graduates of the Career of Nutrition and Community Health of the UTN, period January 2014 - April 2018. Regarding the methodology, was a descriptive, quantitative-qualitative, cross-sectional study. The population, 460 graduates who, through probabilistic sampling, had a participation of 80 graduates. A face-to-face, electronic or telephone survey was applied. The results indicate that 82% of the graduates belong to the female sex, a mixed race ethnic group with 86%. Regarding job placement, 66% work; As for the time to find the first job, it was less than 6 months with 45%. Regarding satisfaction with the academic training received at the UTN, only 22% reported that it was of little use. On the other hand, thequality of teachers, their theoretical foundation, training in practices, availability of time and methodologies used in learning were classified analogously on a scale of good and very good. Only 3% of the study population is conducting postgraduate studies. In conclusion, 2 out of 3 graduates work in their profession. Most rate the knowledge, skills, and abilities acquired in the undergraduate as good and very good.
Keywords: Graduates; Monitoring; Labor Insertion